The potential of anti-vascular endothelial growth factor therapy in metastatic breast cancer: Clinical experience with anti-angiogenic agents, focusing on bevacizumab - Marty, Michel; Pivot, Xavier (European journal of cancer (1990), 2008)
The importance of angiogenesis in tumour growth and development is well known. Overexpression of vascular endothelial growth factor (VEGF), the key mediator of angiogenesis, is associated with poor prognosis in breast cancer. As a result, several therapeutic agents that inhibit the actions of VEGF or its receptors are currently in development for use in metastatic breast cancer (MBC). This review describes the function of VEGF in normal and tumour angiogenesis, explores the rationale behind the use of anti-VEGF therapy in MBC and details the therapeutic impact of such agents on tumour vasculature. Clinical data from trials of anti-VEGF agents in MBC are discussed, with a particular focus on the efficacy and safety of bevacizumab, the anti-VEGF agent at the most advanced stage of development in this tumour type. Future potential uses of bevacizumab in breast cancer are introduced.